Perceptions and attitudes toward clinical trial participation: a study on Moringa oleifera Lam. supplementation in adult HIV patients in Kano State, Nigeria - Gambo, Aisha; Babashani, Musa; Gqaleni, Nceba; Lebina, Limakatso (Frontiers in Pharmacology, 2025)
IntroductionParticipation of patients in well-designed clinical trials forms the essence of all clinical research. PLHIV and receiving ART at AKTH, Kano State, Nigeria, were invited to participate in a six-month Moringa oleifera Lam. supplementation study. One hundred and seventy-seven (177) patients participated, while 27 declined. This study assesses the perception and attitude to clinical trial participation as well as the refusal of the study participants.MethodsA questionnaire interview was conducted on those who participated and those who declined. Data was analysed using both descriptive and inferential statistics.ResultsAll the reasons for participation in clinical trials were statistically significant (p < 0.05). Reasons such as “To help myself” and “To improve my health” both have a perfect mean score of 1.0000 and a standard deviation of 0.0000, indicating reasons as the most important for participation. “To help others” (mean = 1.9379) and “Asked by the doctor” (mean = 2.4237) were moderately endorsed. “For the money” (mean = 3.0000) was the least supported among tangible reasons. Most participants understood the consent form, agreed they gained something from participating, felt respected and treated with dignity, trusted that their information would remain private, and believed the research would benefit others. Participation was largely seen as a free and meaningful choice. The most significant reasons cited for the lack of participation were time constraints (p = 0.029) and lack of money to come to the hospital for the study (p = 0.049).DiscussionClinical trials can be conducted more quickly and effectively with greater patient participation. Improving awareness will improve patient participation and retention in clinical trials, which will invariably increase access to the newest available treatments.